2013
DOI: 10.1111/1462-2920.12227
|View full text |Cite
|
Sign up to set email alerts
|

The Escherichia coli divisome: born to divide

Abstract: SummarySeptation in Escherichia coli involves complex molecular mechanisms that contribute to the accuracy of bacterial division. The proto-ring, a complex made up by the FtsZ, FtsA and ZipA proteins, forms at the beginning of the process and directs the assembly of the full divisome. Central to this complex is the FtsZ protein, a GTPase able to assemble into a ringlike structure that responds to several modulatory inputs including mechanisms to position the septum at midcell. The connection with the cell wall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
30
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 164 publications
(196 reference statements)
1
30
0
4
Order By: Relevance
“…The Gram-negative bacterial divisome is a dynamic macromolecular complex formed by at least 10 essential and up to 15 accessory proteins that assemble at the midcell plane to affect cell division through a series of defined steps, including cell constriction, synthesis of the septal wall, and ultimately cell segregation (1,2). Divisome assembly starts with formation of the FtsZ-ring in the cytoplasm and anchoring of the ring in the inner membrane by FtsA and ZipA.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The Gram-negative bacterial divisome is a dynamic macromolecular complex formed by at least 10 essential and up to 15 accessory proteins that assemble at the midcell plane to affect cell division through a series of defined steps, including cell constriction, synthesis of the septal wall, and ultimately cell segregation (1,2). Divisome assembly starts with formation of the FtsZ-ring in the cytoplasm and anchoring of the ring in the inner membrane by FtsA and ZipA.…”
mentioning
confidence: 99%
“…FtsQ is considered to play a central, yet enigmatic, role in assembly of the divisome through a multitude of transient interactions (1,2). Two-hybrid analyses have suggested that FtsQ interacts with ϳ10 cell division proteins of which the interactions with FtsB and FtsL were confirmed by immunoprecipitation (3).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…FtsZ binds and hydrolyzes GTP in vivo (6) and also polymerizes to form the Z-ring at mid-cell. The Z-ring forms prior to cell division and acts as a scaffold for the recruitment of all downstream cell division proteins; together these comprise the "divisome" (7)(8)(9)(10). In Escherichia coli, the divisome includes ϳ20 essential and nonessential proteins (11)(12)(13).…”
mentioning
confidence: 99%
“…Included in the divisome are the Zaps (FtsZ-associated proteins): ZapA, ZapB, ZapC, and ZapD (14 -19). These Zaps stabilize the Z-ring by increasing lateral interactions between individual filaments, thus bundling FtsZ to provide a scaffold for divisome assembly (9,20).…”
mentioning
confidence: 99%